MATHEMATICAL MODELING AND HEAT TRANSFER IN MHD MAXWELL COUPLE STRESS WILLIAMSON NANOFLUID OVER AN INCLINED PERMEABLE STRETCHING SURFACE - Khan, Ilyas; Rehman, Ali; İnç, Mustafa; Abas, Siti Sabariah Binti; Noor, N. F. M.; Koh, Wei Sin (World Scientific Publ Co Pte Ltd, 2026)
Heat transport in a magnetohydrodynamic (MHD) Maxwell pair stress Williamson nanofluid flowing across a sloped, porous stretched surface is examined in this work using a comprehensive mathematical model. Graphene oxide and molybdenum disulfide nanoparticles are mixed with ethylene glycol, a unique heat-transfer fluid, to create two distinct nanofluids that enhance heat transfer. The stress-fluid model developed by Williamson and Couple describes non-Newtonian behavior. In order to account for the impacts of Maxwell viscoelasticity, pair stress, and non-Newtonian Williamson fluid behavior, a set of NODEs is created from the primary PDEs using similarity transformations (STs). HAM uses semi-numerical simulation approaches to solve the system of nonlinear equations. The study examines the effects of key variables on the speed and temperature profiles, including the Maxwell parameter (MP), Eckert number (EN), thermal radiation (TR), heat source parameter, magnetic field strength, coupling stress, Williamson parameter (WP), and nanoparticle volume friction. As the suction parameter increases, the velocity field (VF) increases; however, as the magnetic field parameter, Maxwell fluid parameter, and WP increase, the VF decreases. The temperature increases in tandem with the TR parameter, heat generation parameter, EN, and volume percentage of nanoparticles. The findings provide suggestions for improving such systems for engineering applications and demonstrate that the addition of nanoparticles significantly increases heat transfer rates. When the present model is compared with the previously published model, they agree favorably, confirming the validity of the current model. The mechanism of heat transport in a nanofluid is revealed by the proposed model.
Keywords: Mathematical Model; Smart Grid; Permeable Surface; MoS2, GO; Nanofluid; Thermal Conductivity (TC); MHD; HAM